Reliability Analysis and ANFIS Computation for Multi-server Redundant Machining System with the Generalized Triadic Policy - Kaur, Chahal Parmeet; Kumar, Kamlesh; Soodan, Bhavneet Singh (Yugoslav Journal of Operations Research, 2023)
The intent of this research is to have discussions about the transient behavior of a multi-server redundant machining system with a generalized Triadic control policy. Furthermore, the system facilitates a multiple working vacation policy for servers. The relevant rates of the associated birth-death process are chosen in order to frame the differential-difference equations for the system. Using the fourth order Runge-Kutta technique, time-dependent probabilities of the states are derived. Some performance metrics of system such as the average number of failed machines, average waiting time of failed machines, and reliability function are established using the states probabilities. Graphical and tabular representations demonstrate the behavior of these metrics with respect to a variety of system characteristics. Statistical hypothesis testing has been employed to compare the outcomes presented in tabular format. Beside these, numerical findings of the Runge-Kutta method are compared to those delivered by an adaptive neuro-fuzzy inference system (ANFIS) technique.